Mechanical stretch regulates TRPC expression and calcium entry in human myometrial smooth muscle cells - Dalrymple, A; Mahn, K; Poston, L; Songu-Mize, E; Tribe, R M (Molecular human reproduction, 2007)
Stretch is known to stimulate myometrial hyperplasia and hypertrophy in early pregnancy and uterine contraction at term. We propose that transduction of the stretch signal involves alteration of intracellular calcium signalling, including changes in transient receptor potential canonical (TRPC) isoform expression. The aim of the present study was to investigate the effect of prolonged mechanical (tonic) stretch in vitro on human myometrial smooth muscle cell calcium signalling and TRPC expression. Cells were cultured from myometrial biopsies, obtained from women undergoing elective Caesarean section at term, grown on Flexiplates and subjected to 25% tonic mechanical stretch for 1, 4 and 14 h. Time-matched control cells were not stretched. Mechanical stretch (14 h) increased basal calcium entry and cyclopiazonic acid (CPA)-induced calcium/Mn(2+) entry (P < 0.05) in Fura-2 loaded cells. The calcium selectivity of CPA-thapsigarin induced inward currents, measured by patch clamp electrophysiology, was also increased in stretched cells compared with control cells (P < 0.05). Real time PCR and Western blot data demonstrated that TRPC3 and TRPC4 mRNA and TRPC3 protein expression were increased by stretch (P < 0.05), respectively. These data support the hypothesis that uterine stretch modulates uterine growth and contractility in pregnancy via alterations in calcium signalling.